Toward a new tribological approach to predict cutting tool wear. Issue 1 (2018) - Rech, J.; Giovenco, A.; Courbon, C.; Cabanettes, F.
Abstract: This work aims at improving the numerical modelling of cutting tool wear in turning. The key improvement consists in identifying a fundamental wear model by means of a dedicated tribometer, able to simulate relevant tribological conditions encountered along the tool–workmaterial interface. Thanks to a design of experiments, the evolution of wear versus time can be assessed for various couples of contact pressure and sliding velocities ( σ n, Vs ) leading to the identification of a new wear model. The latter is implemented in a numerical cutting model to locally simulate tool wear along the contact with regard to each local tribological loading.